The Effect of Designing, Implementing and Evaluating the Pre-Internship Test Using the OSCE Method on Self-Efficacy in the Clinical Performance of Nursing Students - Maryam Momeni; Fatemeh Safari Alamuti; Farnoosh Rashvand (Strides in Development of Medical Education)
Background: Nursing students play a key role in providing care, improving patient health, and making the healthcare system more effective in the future. Therefore, it is important to prepare students in this field to deliver quality care as future nurses. Clinical education can enhance clinical self-efficacy and facilitate appropriate decision-making in nursing students during clinical situations.Objectives: The aim of this study was to determine the effect of a pre-internship test via an objective structured clinical examination (OSCE) on self-efficacy in clinical performance among nursing students.Methods: This single-group quasi-experimental study with a pre- and post-test design was conducted in three steps: design, implementation, and evaluation of the OSCE pre-internship test for undergraduate nursing students. First, a pre-test was administered, followed by student participation in educational workshops. Two weeks later, a post-test was conducted. The evaluation was based on Kirkpatrick's 4-stage model. Data were collected using self-efficacy questionnaires in clinical performance and self-reported feedback from the students. Data analysis was performed using Spearman's, Wilcoxon's, and Friedman's repeated measures tests in SPSS software, with p < 0.05 considered the significance level.Results: The mean scores for the eight stations, as well as the scores for each station individually, increased significantly from the pre-test to the post-test stages (P < 0.001). The mean total score of self-efficacy in clinical performance increased significantly from before the pre-test (79.44 ± 10.29) to immediately after the post-test (100.00 ± 15.98) and three months later (133.96 ± 15.53), with P < 0.001. A significant relationship was observed between the students' GPA in the 7th semester and their pre-internship exam score in the post-test phase (P = 0.001), self-efficacy in clinical performance immediately post-test (P = 0.001), and at three months post-test (P = 0.007). Most nursing students provided positive feedback regarding the test.Conclusion: Performing the OSCE pre-internship test is effective in promoting students' clinical performance and self-efficacy. Therefore, it is suggested to include this exam in the nursing curriculum at the end of the sixth semester.